Grounding Education in Practices of Hope: A Case Study of He Kaupapa Tūmanako - Beban, Alice; Tie, Warwick; Wynyard, Matthew; Trueman, Nicolette; Meikle, Heather (New Zealand Sociology, 2024)
In 2020, in response to the growing expressions of anxiety and hopelessness we saw amongst young people, a team of social scientists at Te Kunenga ki Pūrehuroa | Massey University, Aotearoa New Zealand created an initiative with high school students: “He Kaupapa Tūmanako/Project Hope”. He Kaupapa Tūmanako draws from theoretical traditions in Mātauranga Māori and the Frankfurt School to approach hope as a practice, grounded in the understanding that connection is an antidote to the struggles of our times: connection with other young people, connection with communities, and connection with whenua/land. Over the past four years, we have focused on building He Kaupapa Tūmanako into a suite of courses supported by student mentors that connect young people from around the world. In this article, we reflect on what our experiences are teaching us about engaging hope as a transformative practice in sociology.